Social demands and historiographical production. Writing on the history of the brazilian student movement from two experiences in the brazilian present time - Müller, Angélica (CIAN-Revista de Historia de las Universidades, 2024)
The article shows how a significant part of Brazilian historiographical production on the student movement from the 2000s onwards was performed thanks (and in response) to two different moments in our recent history that resulted from the social demand for memory, truth, and justice: the first, the development of the Student Movement Memory Project (Projeto Memória do Movimento Estudantil) in the early 2000s; the second is the period since the establishment of the National Truth Commission (Comissão Nacional da Verdade), in 2012. In order to do this, there is an introductory overview of the first works from the 1980s, focusing on the study of the National Union of Students in the 1960s, to show how research on SM became more comprehensive (and more in-depth), especially through the expansion and opening of archives, notably in the construction of oral collections. The main analysis focuses on the presentation and development of these two initiatives. Finally, the article makes some considerations about this overview by signaling some connections between social demand and historiographic production, which is characteristic of the history of the present time, and pointing out themes and study objec that are still worthy of further investigation.